2013
DOI: 10.3109/17518423.2013.830653
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of lower extremity orthoses on energy expenditure in patients with cerebral palsy

Abstract: It was concluded that especially solid PAFO can be more beneficial in terms of energy consumption in CP patients. In rehabilitation phase, the EEI measurement was seen to be a useful and practical method for choosing the proper orthosis type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…It has been shown that a light-weight plastic AFO requires less energy expenditure and provides a higher walking velocity than a heavier AFO (25). A solid AFO is also more beneficial in terms of energy consumption (26). In the current study, there was a higher rate of continued orthosis use with pAFO (4 of 6) than with mAFO (3 of 6).…”
Section: Discussionmentioning
confidence: 63%
“…It has been shown that a light-weight plastic AFO requires less energy expenditure and provides a higher walking velocity than a heavier AFO (25). A solid AFO is also more beneficial in terms of energy consumption (26). In the current study, there was a higher rate of continued orthosis use with pAFO (4 of 6) than with mAFO (3 of 6).…”
Section: Discussionmentioning
confidence: 63%
“…The ankle foot orthoses are widely used for children with cerebral palsy and could improve the gait efficiency [ 25 ]. The orthosis structure, which restricts range of motion of ankle, could increase the ankle joint stability and position control [ 9 ]. In spatiotemporal findings of the study of Buckon et al [ 26 ], a solid ground reaction ankle foot orthosis for children with cerebral palsy produced a significant increase of 0.06 m in stride length, but decreases of 0.04 m/s and 18 steps/min in gait speed and cadence, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of walking aids is very important for children with cerebral palsy when walking. In previous study, solid ground reaction ankle foot orthoses have been used to help children with cerebral palsy to walk [ 9 ]. Solid ground reaction ankle foot orthoses are devices designed to increase the knee extension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations